The Correlation Among Students' Learning Styles And Students' Motivation In Learning English With Their Vocabulary Mastery - Tri Saswandi; Ariana Oktavia; Deni Abdillah. M; Wahyu Wijayati; Rahmat Jaya (Departement of Mathematics Education, 2023)
This study aimed to examine the relationship between students' learning style and motivation when learning English, and their proficiency in vocabulary during their third semester in the English Education program at the State Islamic Institute of Kerinci in the academic year 2022-2023. The study was of a quantitative nature. The population of the study consisted of students in their third semester of the English Department at IAIN Kerinci. The sample size used for the research was 32 students, who were selected via total sampling. Data collection on learning styles was conducted using Gutman's questionnaire, while motivation was gathered through the Likert scale. Vocabulary acquisition was examined through a test. SPSS 26 was utilized to analyze the data using a correlation and regression test. The report found that 86.25% of the third-semester students of the English Education Program of the State Islamic Institute of Kerinci used the Visual Auditory Kinesthetic (VAK) learning style. The students' motivation was in the high criteria, with a score of 72.73. Also, the average score of 80 indicated excellent vocabulary mastery, rated with the criteria of A. The study yielded significant results, indicating a high correlation between the students' learning style and their vocabulary acquisition. Moreover, a more significant correlation was observed between the students' learning styles and vocabulary mastery, as well as with their motivation levels. In conclusion, the results of the study suggest that an appropriate choice of learning style can considerably enhance students' vocabulary acquisition during their third semester in the English Education Program at the State Islamic Institute of Kerinci in the 2022-2023 academic year.